Using Repeated Reading Strategy: Its Effect on Students’ Reading Comprehension at SMAN 19 Pekanbaru - Nuzul Izka Nofrisa; Tri Adinda Novela; Anisa Faizah Avrilia; Imelda Mahera; Awliya Dara Fitriadi; Rizki Amelia (Journal of Education and Learning Research, 2026)
This study investigates the effect of the Repeated Reading Strategy on students’ reading comprehension in an EFL context. The study was motivated by students’ low reading comprehension ability, particularly in understanding vocabulary and comprehending narrative texts.This research employed a quantitative approach with a quasi-experimental design involving an experimental class and a control class. The participants were 82 eleventh-grade students at SMAN 19 Pekanbaru selected through purposive sampling. Data were collected using a 20-item multiple-choice reading comprehension test based on five indicators: identifying main ideas, finding factual information, understanding vocabulary, recognizing references, and making inferences. The instrument was tested for validity and reliability, with the Cronbach’s Alpha coefficient showing a reliability score of 0.744. The data were analyzed using descriptive statistics and an independent sample t-test with SPSS version 25. The findings revealed that the experimental class showed greater improvement than the control class. The mean score of the experimental class increased from 60.73 to 77.32, while the control class obtained a lower post-test mean score of 69.15. In addition, the independent sample t-test showed a significance value of 0.009 (< 0.05), indicating a significant difference between the two groups.The study concludes that the Repeated Reading Strategy is effective in improving students’ reading comprehension in the Indonesian EFL context. Unlike previous studies that mainly focused on elementary and junior high school students, this study provides empirical evidence of the effectiveness of repeated reading at the senior high school level, particularly in improving comprehension of narrative texts.